2012
DOI: 10.1016/j.molcel.2012.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Control of Proinflammatory Gene Programs by Regulated Trimethylation and Demethylation of Histone H4K20

Abstract: Summary Regulation of genes that initiate and amplify inflammatory programs of gene expression is achieved by signal-dependent exchange of co-regulator complexes that function to read, write and erase specific histone modifications linked to transcriptional activation or repression. Here, we provide evidence for the role of trimethylated histone H4 lysine 20 (H4K20me3) as a repression checkpoint that restricts expression of toll like receptor 4 (TLR4) target genes in macrophages. H4K20me3 is deposited at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
210
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(218 citation statements)
references
References 48 publications
5
210
2
1
Order By: Relevance
“…Transcription elongation NSD1, NSD2 [263] , SET2 [264] , SMYD2 [232] , MMSET [265] ASH1 [266] , JHDM1 [267] , JHDM1A/KDM2A, JHDM1B/KDM2B [268] ISW1B [269] H4K20 me1 me2 me3 (non-genic regions, centromeric heterochromatin, satellite sequences, long terminal repeats Transcritional silencing, heterochromatin, repression of proinflammatory genes PR-SET7/SET8 [270] SUV420H1, SUV420H2 [274] SUV420H2 [274] , SMYD5 [275] PHF8 [271] PHF2 [275] PHF2 [275] L3MBTL1 [272] PHF20 [276] , L3MBTL1 [277] NcoR [275] [ gene [158] . Furthermore, it is well known that a considerable amount of integrated vectors become silent [159] , and this effect seems to be dependent on the promoter chosen to drive the ectopic expression of the gene [160,161] .…”
Section: H3k27me3 or H3k9me3mentioning
confidence: 99%
“…Transcription elongation NSD1, NSD2 [263] , SET2 [264] , SMYD2 [232] , MMSET [265] ASH1 [266] , JHDM1 [267] , JHDM1A/KDM2A, JHDM1B/KDM2B [268] ISW1B [269] H4K20 me1 me2 me3 (non-genic regions, centromeric heterochromatin, satellite sequences, long terminal repeats Transcritional silencing, heterochromatin, repression of proinflammatory genes PR-SET7/SET8 [270] SUV420H1, SUV420H2 [274] SUV420H2 [274] , SMYD5 [275] PHF8 [271] PHF2 [275] PHF2 [275] L3MBTL1 [272] PHF20 [276] , L3MBTL1 [277] NcoR [275] [ gene [158] . Furthermore, it is well known that a considerable amount of integrated vectors become silent [159] , and this effect seems to be dependent on the promoter chosen to drive the ectopic expression of the gene [160,161] .…”
Section: H3k27me3 or H3k9me3mentioning
confidence: 99%
“…Interestingly, shRNAs targeting three genes were recovered in both rounds of screening, strongly suggesting that these genes must be inactivated for exit from dormancy. Intriguingly, the genes targeted by these shRNAs constitute the Notch inhibitor Numb (34,35), the histone methyl transferase Smyd5 (36), and the Smad E3 ubiquitin ligase Smurf2 (37). Because it is well established that Smurf2 antagonizes TGF-β signaling, which promotes metastasis (2, 37), we focused on Numb and Smyd5.…”
Section: Gain-of-function Screens Identify Micrornas That Promote Metmentioning
confidence: 99%
“…In other studies, PHF2 has been respectively reported to exhibit an H3K9me1-specific activity (17), a protein kinase A (PKA)-dependent H3K9me2 demethylase activity (26), and H4K20me3 demethylase activity (27). In addition to the JmjC domain, PHF2, PHF8, and KIAA1718 are unique among the JmjC family proteins with possession of an N-terminal PHD (plant homeodomain) domain.…”
mentioning
confidence: 99%
“…PHF8 was shown to interact with UBF and facilitate rDNA transcription, depending on its H3K4me3 binding and H3K9me1/2 demethylase activity (13,17,18), whereas PHF2 was also shown to activate rDNA transcription, depending on its H3K4me3 binding activity (17). In addition, PHF8 has been shown to interact with specific transcription factors, such as RAR␣ (21) and NOTCH1 intracellular domain (30), as well as RNA polymerase II (Pol II) (28) and functions as a coactivator, whereas PHF2 has been shown to interact with CEBPA to regulate adipogenesis (31), with ARID5B to regulate PKA-dependent gene induction of Pepck and G6Pase (26), and with NF-B to regulate proinflammatory gene programs (27).…”
mentioning
confidence: 99%